Supported metal monatomic catalyst as well as preparation method and application thereof

By loading the cloth transition metal single atoms on the copper sulfide support and coordinating with the sulfur element, the problem of easy agglomeration of metal single atoms in the supported catalyst is solved, high loading and uniform dispersion are achieved, and catalytic performance and stability are improved.

CN119633851APending Publication Date: 2025-03-18NORTH CHINA ELECTRIC POWER UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411705194.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In supported catalysts, metal single atoms are prone to migrating and agglomeration, resulting in deterioration of catalytic activity and degradation of stability. The loading of existing metal single atom catalysts is low and the catalytic performance is poor.

Method used

By using copper sulfide as a support, combining the coordination between transition metal single atoms (such as platinum group metal single atoms and rhenium metal single atoms) with sulfur, the uniform distribution of metal single atoms under high load conditions is achieved, avoiding the formation of clusters or nanoparticles.

Benefits of technology

The high loading and uniform dispersion of metal single atom catalysts is achieved, the catalytic performance and stability are improved, and the types and loading of metal single atoms can be regulated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633851A_ABST
    Figure CN119633851A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of monatomic nano-catalysts, and particularly relates to a supported metal monatomic catalyst as well as a preparation method and application thereof. The supported metal monatomic catalyst provided by the invention comprises copper sulfide and transition metal monatomic supported on the surface of the copper sulfide, and the transition metal monatomic comprises platinum group metal monatomic and / or rhenium metal monatomic; the loading capacity of the transition metal monatomic is greater than or equal to 0.3 at%. The loading capacity of the transition metal monatomic in the supported metal monatomic catalyst provided by the invention can reach 12.4 at%. Compared with the prior art, the catalyst provided by the invention is controllable in microstructure, uniform in monatomic dispersion and high in loading capacity, and the adjustability of metal monatomic types and the loading capacity is realized. The preparation method disclosed by the invention has the characteristics of mild reaction conditions, simple steps, easiness in large-scale production and the like, and has important scientific and engineering significance in metal monatomic catalysis research.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of single-atom nanocatalysts, and in particular relates to a supported metal single-atom catalyst and a preparation method and application thereof. Background Art

[0002] It is urgent to develop clean, efficient and sustainable new energy technologies. Electrochemistry is an important technology for achieving clean preparation, conversion and storage of renewable energy. For example, fuel cells, water electrolysis to produce hydrogen and zinc-air batteries. The energy efficiency of these energy conversion devices usually depends on the speed of each catalytic reaction, and the activity of the catalytic reaction depends to a large extent on the catalyst. In the history of catalyst research, nanomaterials have unique advantages in accelerating the process of catalytic reactions.

[0003] In order to further improve the catalytic performance of catalysts, researchers have continuously regulated the morphology, crystal surface, and size of catalysts to maximize the exposure of more active sites. Among them, single-atom metal catalysts (SACs) have great potential in various energy catalysis applications due to their high utilization rate of metal atoms, which makes the catalysts highly active and highly selective.

[0004] However, as the size of nanoparticles decreases, the surface free energy increases dramatically, making it easy for single metal atoms to migrate and agglomerate to form nanoclusters or nanoparticles, which results in the deterioration of the catalytic activity of the unit metal, causing the catalyst to lose activity and decrease in stability.

[0005] Therefore, in supported catalysts, metal single atoms can easily migrate and aggregate to form nanoclusters or nanoparticles under high loading conditions. Currently, the loading amount of metal single atom catalysts is low and the catalytic performance is poor. Summary of the invention

[0006] The purpose of the present invention is to provide a supported metal single atom catalyst and a preparation method and application thereof. The supported metal single atom catalyst provided by the present invention has uniformly dispersed single atoms and a high loading amount, and the type and loading amount of the metal single atoms can be controlled.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a supported metal single atom catalyst, comprising copper sulfide and transition metal single atoms supported on the surface of the copper sulfide, wherein the transition metal single atoms include platinum group metal single atoms and / or rhenium metal single atoms; and the loading amount of the transition metal single atoms is ≥0.3at%.

[0009] Preferably, the platinum group metal single atom includes one or more of an osmium metal single atom, a rhodium metal single atom, a platinum metal single atom, an iridium metal single atom and a ruthenium metal single atom.

[0010] Preferably, the loading amount of the transition metal single atom is 0.3 to 12.4 at %.

[0011] Preferably, the copper sulfide has a diameter of 10 to 15 nm and a thickness of 2 to 3 nm.

[0012] The present invention provides a method for preparing the supported metal single-atom catalyst described in the above technical solution, comprising the following steps:

[0013] mixing an organic copper salt, sulfur powder, a transition metal organic precursor and an organic solvent to obtain a dispersed solution;

[0014] The dispersed solution is heated to react to obtain the supported metal single atom catalyst.

[0015] Preferably, the organic copper salt is copper acetylacetonate; the transition metal organic precursor includes one or more of iridium acetylacetonate, rhodium acetylacetonate, ruthenium acetylacetonate, platinum acetylacetonate, triosmium dodecacarbonyl and dirhenium dodecacarbonyl;

[0016] The organic solvent includes one or more of oleic acid, oleylamine, ethylene glycol and benzyl alcohol.

[0017] Preferably, in the dispersed solution: the mass concentration of the organic copper salt is 2-2.5 mg / mL, the mass concentration of the sulfur powder is 0.5-0.6 mg / mL, and the mass concentration of the transition metal organic precursor is 0.2-4 mg / mL.

[0018] Preferably, the reaction temperature is 180-220° C., and the insulation time is 60-120 min.

[0019] Preferably, a colloidal reaction product is directly obtained after the reaction is completed; and the method further comprises: post-treating the colloidal reaction product with an organic reagent to obtain the supported metal single atom catalyst; the organic reagent comprises cyclohexane and ethanol, and the volume ratio of cyclohexane to ethanol is 1:1 to 3.

[0020] The present invention provides the use of the supported metal single atom catalyst described in the above technical solution or the supported metal single atom catalyst prepared by the preparation method described in the above technical solution in energy catalysis.

[0021] The present invention provides a supported metal single atom catalyst, comprising copper sulfide and transition metal single atoms supported on the surface of the copper sulfide, wherein the transition metal single atoms include platinum group metal single atoms and / or rhenium metal single atoms; the loading amount of the transition metal single atoms is ≥0.3at%. The present invention uses copper sulfide as a catalyst carrier, and through the coordination of transition metal single atoms (i.e. platinum group metal single atoms and / or rhenium metal single atoms) with the sulfur element in the copper sulfide (i.e. the transition metal single atoms in the supported metal single atom catalyst provided by the present invention coordinate with the sulfur element in the copper sulfide), the transition metal single atoms can be evenly distributed in a single atom state on the surface of the copper sulfide under the condition of a higher loading amount, without forming clusters or nanoparticles. The results of the embodiment show that the loading amount of the transition metal single atoms in the supported metal single atom catalyst provided by the present invention can reach 12.4at%. Compared with the prior art, the catalyst provided by the present invention has a controllable microstructure, uniform single atom dispersion, high loading amount, and realizes the controllability of the metal single atom type and loading amount, which has important scientific and engineering significance in the research of metal single atom catalysis.

[0022] The present invention provides a method for preparing a supported metal single atom catalyst according to the above technical solution, comprising the following steps: mixing an organic copper salt, sulfur powder, a transition metal organic precursor and an organic solvent to obtain a dispersed solution; heating the dispersed solution for reaction to obtain the supported metal single atom catalyst. The preparation method provided by the present invention is based on a wet chemistry-sol-gel preparation method, and a supported catalyst carrying atomic-level metal single atoms is prepared by a one-step reduction method, which has the characteristics of simple operation and easy scalability.

[0023] Furthermore, in the present invention, the reaction temperature is 180-220° C. The preparation method provided by the present invention has mild reaction conditions and effectively avoids problems such as metal agglomeration caused by high-temperature calcination. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a transmission electron microscope image of the copper sulfide nanosheet-loaded osmium metal single-atom catalyst (loading amount is 12.4 at%) prepared in the present invention;

[0025] Figure 2 This is a transmission electron microscope image of the copper sulfide nanosheet-loaded osmium metal single-atom catalyst (loading amount is 12.4 at%) prepared in the present invention;

[0026] Figure 3 This is an aberration-corrected high-angle annular dark field image of the copper sulfide nanosheet-loaded osmium metal single-atom catalyst (loading amount is 12.4 at%) prepared by the present invention;

[0027] Figure 4The X-ray diffraction pattern of the copper sulfide nanosheet-loaded osmium metal single-atom catalyst (loading amount is 12.4 at%) prepared by the present invention;

[0028] Figure 5 This is a transmission electron microscopy image of the copper sulfide nanosheet-supported rhodium metal single-atom catalyst (loading amount is 12.4 at %) prepared in Example 2 of the present invention;

[0029] Figure 6 This is a transmission electron microscopy image of the copper sulfide nanosheet-supported platinum metal single-atom catalyst (loading amount is 12.4 at %) prepared in Example 3 of the present invention;

[0030] Figure 7 This is a transmission electron microscopy image of the copper sulfide nanosheets loaded with iridium metal single atom catalyst (loading amount is 12.4 at %) prepared in Example 4 of the present invention;

[0031] Figure 8 This is a transmission electron microscopy image of the copper sulfide nanosheet-supported ruthenium metal single-atom catalyst (loading amount is 12.4 at %) prepared in Example 5 of the present invention;

[0032] Fig. 9 This is a transmission electron microscopy image of the copper sulfide nanosheet-supported rhenium metal single-atom catalyst (loading amount is 12.4 at %) prepared in Example 6 of the present invention;

[0033] Fig.10 The transmission electron microscope image of the product obtained when the mass ratio of copper salt to sulfur powder in Comparative Example 3 is 12:1 (sulfur powder is 0.2 mg / mL, triosmium dodecacarbonyl is 4 mg / mL);

[0034] Fig.11 This is a transmission electron microscope image of the product obtained when the mass ratio of copper salt to sulfur powder in Comparative Example 4 is 2:1 (sulfur powder is 1.2 mg / mL, triosmium dodecacarbonyl is 4 mg / mL). DETAILED DESCRIPTION

[0035] The present invention provides a supported metal single atom catalyst, comprising copper sulfide and transition metal single atoms supported on the surface of the copper sulfide, wherein the transition metal single atoms include platinum group metal single atoms and / or rhenium metal single atoms; and the loading amount of the transition metal single atoms is ≥0.3at%.

[0036] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0037] The supported metal single atom catalyst provided by the present invention includes copper sulfide. In the present invention, the copper sulfide is used as a carrier of the supported metal single atom catalyst. In the present invention, the copper sulfide has a two-dimensional nanosheet morphology, and the diameter of the copper sulfide is preferably 10 to 15 nm, and the thickness is preferably 2 to 3 nm.

[0038] The supported metal single atom catalyst provided by the present invention comprises a transition metal single atom supported on the surface of the copper sulfide. In the present invention, the transition metal single atom is coordinated with the sulfur element in the copper sulfide. The transition metal single atom comprises a platinum group metal single atom and / or a rhenium metal single atom. The platinum group metal single atom preferably comprises one or more of an osmium metal single atom, a rhodium metal single atom, a platinum metal single atom, an iridium metal single atom and a ruthenium metal single atom. In a specific embodiment of the present invention, the transition metal single atom is specifically one or more of an osmium metal single atom, a rhodium metal single atom, a platinum metal single atom, an iridium metal single atom, a ruthenium metal single atom and a rhenium metal single atom. The loading amount of the transition metal single atom is ≥0.3at%, preferably 0.3-12.4at%, and in the embodiment is specifically 0.3at%, 4.2at%, 8.5at% or 12.4at%. In the present invention, the loading amount of the transition metal single atom is the percentage of the number of atoms of the transition metal single atom to the total number of atoms of the transition metal single atom and the number of atoms of copper sulfide.

[0039] In the present invention, the supported metal single atom catalyst has a two-dimensional nanosheet morphology. The supported metal single atom catalyst preferably has a diameter of 10 to 15 nm and a thickness of 2 to 3 nm.

[0040] In a specific embodiment of the present invention, the supported metal single atom catalyst is specifically copper sulfide nanosheets loaded with osmium metal single atoms, copper sulfide nanosheets loaded with rhodium metal single atoms, copper sulfide nanosheets loaded with platinum metal single atoms, copper sulfide nanosheets loaded with iridium metal single atoms, copper sulfide nanosheets loaded with ruthenium metal single atoms or copper sulfide nanosheets loaded with rhenium metal single atoms.

[0041] The supported metal single atom catalyst provided by the present invention has copper sulfide structure and two-dimensional nanosheet morphology characteristics; wherein the copper sulfide nanosheet supported metal exists in the form of single atoms, and the single atoms are coordinated with sulfur without forming clusters or nanoparticles.

[0042] The present invention provides a method for preparing the supported metal single-atom catalyst described in the above technical solution, comprising the following steps:

[0043] mixing an organic copper salt, sulfur powder, a transition metal organic precursor and an organic solvent to obtain a dispersed solution;

[0044] The dispersed solution is heated to react to obtain the supported metal single atom catalyst.

[0045] The present invention mixes an organic copper salt, sulfur powder, a transition metal organic precursor and an organic solvent to obtain a dispersed solution. In the present invention, the organic copper salt is preferably copper acetylacetonate. The transition metal organic precursor preferably includes one or more of iridium acetylacetonate, rhodium acetylacetonate, ruthenium acetylacetonate, platinum acetylacetonate, triosmium dodecacarbonyl and dirhenium dodecacarbonyl. The organic solvent preferably includes one or more of oleic acid, oleylamine, ethylene glycol and benzyl alcohol. The mixing is preferably carried out under ultrasonic conditions, and the ultrasonic time is preferably 20 to 60 minutes, and specifically 30 minutes in the embodiment. In the present invention, in the dispersed solution: the mass concentration of the organic copper salt is preferably 2 to 2.5 mg / mL, and specifically 2.4 mg / mL in the embodiment; the mass concentration of the sulfur powder is preferably 0.5 to 0.6 mg / mL, and specifically 0.6 mg / mL in the embodiment; the mass concentration of the transition metal organic precursor is preferably 0.2 to 4 mg / mL, and specifically 0.2 mg / mL, 1 mg / mL, 2 mg / mL or 4 mg / mL in the embodiment. In the present invention, the mass ratio of the organic copper salt to the sulfur powder is preferably (2-2.5): (0.5-0.6), and specifically 2.4:0.6 in the embodiment. The present invention can obtain a copper sulfide carrier with a more uniform nanosheet morphology (preferably 10-15 nm in diameter and 2-3 nm in thickness) by controlling the mass ratio of the organic copper salt to the sulfur powder, thereby forming a larger space for loading transition metal single atoms.

[0046] After obtaining the dispersed solution, the present invention heats the dispersed solution for reaction to obtain the supported metal single atom catalyst. In the present invention, the reaction temperature is preferably 180 to 220° C., and the insulation time is preferably 60 to 120 minutes.

[0047] In the present invention, a colloidal reaction product is directly obtained after the reaction is completed; the present invention preferably further comprises: post-treating the colloidal reaction product with an organic reagent to obtain the supported metal single atom catalyst. The organic reagent preferably comprises cyclohexane and ethanol, and the volume ratio of cyclohexane to ethanol is preferably 1:1 to 3, and specifically 1:3 in the embodiment. In the present invention, the post-treatment preferably comprises the following steps: centrifuging the colloidal reaction product and the organic reagent, and then washing with the organic reagent. The rotation speed of the centrifugal treatment is preferably 8500 to 9500 r / min, and the time of the centrifugal treatment is preferably 5 to 10 min. The number of washings is preferably 2 to 3 times.

[0048] Compared with the prior art, the preparation method of the supported metal single atom catalyst provided by the present invention has the following beneficial technical effects:

[0049] (1) The preparation conditions are mild (180-220°C) and the operation is simple (one-pot method), which effectively avoids problems such as metal agglomeration caused by high-temperature calcination.

[0050] (2) For the first time, two-dimensional copper sulfide nanosheets loaded with platinum group metal single atom catalysts were prepared. The catalyst nanosheets had a diameter of 10 to 15 nm and a thickness of 2 to 3 nm.

[0051] (3) The present invention can prepare a series of copper sulfide nanosheet catalysts loaded with metal single atoms.

[0052] The present invention provides the use of the supported metal single atom catalyst described in the above technical solution or the supported metal single atom catalyst prepared by the preparation method described in the above technical solution in energy catalysis.

[0053] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0054] Example 1

[0055] 1) dissolving copper acetylacetonate, sulfur powder and triosmium dodecacarbonyl in an organic solvent at concentrations of 2.4 mg / mL, 0.6 mg / mL and 0.2-4 mg / mL (specifically 0.2 mg / mL, 1 mg / mL, 2 mg / mL or 4 mg / mL in this embodiment) respectively, and ultrasonicating for 20 minutes to prepare a uniform colloidal solution;

[0056] 2) The dispersion obtained in step 1 is transferred to an oil bath pot for oil bath heating. After the dispersion is heated to 180° C., it is kept warm. The dispersion is allowed to react at 180° C. for 60 minutes to generate a black colloidal solution. The heating is then stopped. After the reaction container is cooled to room temperature, a cyclohexane / ethanol mixed solution with a volume ratio of 1:3 is added to the black colloidal solution, followed by centrifugation at 9500 r / min for 5 minutes, and then washed twice with a cyclohexane / ethanol mixed solution to obtain a copper sulfide nanosheet-loaded osmium metal single atom catalyst.

[0057] In this embodiment, the mass concentration of triosmium dodecacarbonyl is 0.2 mg / mL, and the loading amount of osmium metal single atoms in the prepared copper sulfide nanosheet-supported osmium metal single atom catalyst is 0.3 at%;

[0058] The mass concentration of triosmium dodecacarbonyl is 1 mg / mL, and the loading amount of osmium metal single atoms in the prepared copper sulfide nanosheet-supported osmium metal single atom catalyst is 4.2 at%;

[0059] The mass concentration of triosmium dodecacarbonyl is 2 mg / mL, and the loading amount of osmium metal single atoms in the prepared copper sulfide nanosheet-supported osmium metal single atom catalyst is 8.5 at%;

[0060] The mass concentration of triosmium dodecacarbonyl is 4 mg / mL, and the loading amount of osmium metal single atoms in the prepared copper sulfide nanosheet-supported osmium metal single atom catalyst is 12.4 at %.

[0061] Figure 1 and Figure 2 The morphology and structural characteristics of the copper sulfide nanosheet-loaded osmium metal single-atom catalyst (loading amount is 12.4 at%) prepared in Example 1 of the present invention are shown. It has a nanometer-sized diameter and a two-dimensional nanosheet morphology, with a diameter of about 10 to 15 nm and a thickness of 2 to 3 nm. Figure 3 It shows that the copper sulfide nanosheet-supported osmium metal single atom catalyst (loading amount is 12.4 at %) exists in the form of single atoms, and the red circles indicate isolated atoms. Figure 4 This indicates that the copper sulfide nanosheet-loaded osmium metal single-atom catalyst (loading amount is 12.4at%) is a copper sulfide single-phase solid solution structure.

[0062] Example 2

[0063] 1) dissolving copper acetylacetonate, sulfur powder and rhodium acetylacetonate in an organic solvent at concentrations of 2.4 mg / mL, 0.6 mg / mL and 0.2-4 mg / mL (specifically 0.2 mg / mL, 1 mg / mL, 2 mg / mL or 4 mg / mL in this embodiment) respectively, and ultrasonicating for 20 minutes to prepare a turbid and uniform colloidal solution;

[0064] 2) The dispersion obtained in step 1 is transferred to an oil bath pot for oil bath heating. After the dispersion is heated to 180° C., it is kept warm. The dispersion is allowed to react at 180° C. for 60 minutes to generate a black colloidal solution. The heating is then stopped. After the reaction container is cooled to room temperature, a cyclohexane / ethanol mixed solution with a volume ratio of 1:3 is added to the black colloidal solution. The solution is then centrifuged at 9500 r / min for 5 minutes and then washed twice with the cyclohexane / ethanol mixed solution to obtain a copper sulfide nanosheet-loaded rhodium metal single atom catalyst.

[0065] In this embodiment, the mass concentration of rhodium acetylacetonate is 0.2 mg / mL, and the loading amount of rhodium metal single atoms in the prepared copper sulfide nanosheet-supported rhodium metal single atom catalyst is 0.3 at%;

[0066] The mass concentration of rhodium acetylacetonate is 1 mg / mL, and the loading amount of rhodium metal single atoms in the prepared copper sulfide nanosheet-supported rhodium metal single atom catalyst is 4.2 at%;

[0067] The mass concentration of rhodium acetylacetonate is 2 mg / mL, and the loading amount of rhodium metal single atoms in the prepared copper sulfide nanosheet-supported rhodium metal single atom catalyst is 8.5 at%;

[0068] The mass concentration of rhodium acetylacetonate is 4 mg / mL, and the loading amount of rhodium metal single atoms in the prepared copper sulfide nanosheet-supported rhodium metal single atom catalyst is 12.4 at %.

[0069] Example 3

[0070] 1) copper acetylacetonate, sulfur powder and platinum acetylacetonate were dissolved in an organic solvent at a concentration of 2.4 mg / mL, 0.6 mg / mL and 0.2-4 mg / mL (specifically 0.2 mg / mL, 1 mg / mL, 2 mg / mL or 4 mg / mL in this embodiment), respectively, and ultrasonicated for 20 minutes to prepare a turbid and uniform colloidal solution;

[0071] 2) The dispersion obtained in step 1 is transferred to an oil bath pot for oil bath heating. After the dispersion is heated to 180° C., it is kept warm. The dispersion is allowed to react at 180° C. for 60 minutes to generate a black colloidal solution. The heating is then stopped. After the reaction container is cooled to room temperature, a cyclohexane / ethanol mixed solution with a volume ratio of 1:3 is added to the black colloidal solution. The solution is then centrifuged at 9500 r / min for 5 minutes and then washed twice with the cyclohexane / ethanol mixed solution to obtain a copper sulfide nanosheet-supported platinum metal single atom catalyst.

[0072] In this embodiment, the mass concentration of platinum acetylacetonate is 0.2 mg / mL, and the loading amount of platinum metal single atoms in the prepared copper sulfide nanosheet-supported platinum metal single atom catalyst is 0.3 at%;

[0073] The mass concentration of platinum acetylacetonate is 1 mg / mL, and the loading amount of platinum metal single atoms in the prepared copper sulfide nanosheet-supported platinum metal single atom catalyst is 4.2 at%;

[0074] The mass concentration of platinum acetylacetonate is 2 mg / mL, and the loading amount of platinum metal single atoms in the prepared copper sulfide nanosheet-supported platinum metal single atom catalyst is 8.5 at%;

[0075] The mass concentration of platinum acetylacetonate is 4 mg / mL, and the loading amount of platinum metal single atoms in the prepared copper sulfide nanosheet-supported platinum metal single atom catalyst is 12.4 at %.

[0076] Example 4

[0077] 1) dissolving copper acetylacetonate, sulfur powder and iridium acetylacetonate in an organic solvent at concentrations of 2.4 mg / mL, 0.6 mg / mL and 0.2-4 mg / mL (specifically 0.2 mg / mL, 1 mg / mL, 2 mg / mL or 4 mg / mL in this embodiment) respectively, and ultrasonicating for 60 min to prepare a turbid and uniform colloidal solution;

[0078] 2) The dispersion obtained in step 1 is transferred to an oil bath pot for oil bath heating. After the dispersion is heated to 220° C., it is kept warm. The dispersion is allowed to react at 220° C. for 120 min to generate a black colloidal solution. The heating is then stopped. After the reaction container is cooled to room temperature, a cyclohexane / ethanol mixed solution with a volume ratio of 1:3 is added to the black colloidal solution. The solution is then centrifuged at 8500 r / min for 5 min, and then washed twice with the cyclohexane / ethanol mixed solution to obtain a copper sulfide nanosheet-loaded iridium metal single atom catalyst.

[0079] In this embodiment, the mass concentration of iridium acetylacetonate is 0.2 mg / mL, and the loading amount of iridium metal single atoms in the prepared copper sulfide nanosheet-supported iridium metal single atom catalyst is 0.3 at%;

[0080] The mass concentration of iridium acetylacetonate is 1 mg / mL, and the loading amount of iridium metal single atoms in the prepared copper sulfide nanosheet-supported iridium metal single atom catalyst is 4.2 at%;

[0081] The mass concentration of iridium acetylacetonate is 2 mg / mL, and the loading amount of iridium metal single atoms in the prepared copper sulfide nanosheet-supported iridium metal single atom catalyst is 8.5 at%;

[0082] The mass concentration of iridium acetylacetonate is 4 mg / mL, and the loading amount of iridium metal single atoms in the prepared copper sulfide nanosheet-supported iridium metal single atom catalyst is 12.4 at %.

[0083] Example 5

[0084] 1) dissolving copper acetylacetonate, sulfur powder and ruthenium acetylacetonate in an organic solvent at concentrations of 2.4 mg / mL, 0.6 mg / mL and 0.2-4 mg / mL, respectively, and ultrasonicating for 60 min to prepare a turbid and uniform colloidal solution;

[0085] 2) The dispersion obtained in step 1 is transferred to an oil bath pot for oil bath heating. After the dispersion is heated to 220° C., it is kept warm. The dispersion is allowed to react at 220° C. for 120 min to generate a black colloidal solution. The heating is then stopped. After the reaction container is cooled to room temperature, a cyclohexane / ethanol mixed solution with a volume ratio of 1:3 is added to the black colloidal solution. The solution is then centrifuged at 8500 r / min for 5 min, and then washed twice with the cyclohexane / ethanol mixed solution to obtain a copper sulfide nanosheet-loaded ruthenium metal single atom catalyst.

[0086] In this embodiment, the mass concentration of ruthenium acetylacetonate is 0.2 mg / mL, and the loading amount of ruthenium metal single atoms in the prepared copper sulfide nanosheet-supported ruthenium metal single atom catalyst is 0.3 at%;

[0087] The mass concentration of ruthenium acetylacetonate is 1 mg / mL, and the loading amount of ruthenium metal single atoms in the prepared copper sulfide nanosheet-supported ruthenium metal single atom catalyst is 4.2 at%;

[0088] The mass concentration of ruthenium acetylacetonate is 2 mg / mL, and the loading amount of ruthenium metal single atoms in the prepared copper sulfide nanosheet-supported ruthenium metal single atom catalyst is 8.5 at%;

[0089] The mass concentration of ruthenium acetylacetonate is 4 mg / mL, and the loading amount of ruthenium metal single atoms in the prepared copper sulfide nanosheet-supported ruthenium metal single atom catalyst is 12.4 at %.

[0090] Example 6

[0091] 1) dissolving copper acetylacetonate, sulfur powder and dodecacarbonyl dirhenium in an organic solvent at concentrations of 2.4 mg / mL, 0.6 mg / mL and 0.2-4 mg / mL (specifically 0.2 mg / mL, 1 mg / mL, 2 mg / mL or 4 mg / mL in this embodiment) respectively, and ultrasonicating for 60 minutes to prepare a turbid and uniform colloidal solution;

[0092] 2) The dispersion obtained in step 1 is transferred to an oil bath pot for oil bath heating. After the dispersion is heated to 220° C., it is kept warm. The dispersion is allowed to react at 220° C. for 120 min to generate a black colloidal solution. The heating is then stopped. After the reaction container is cooled to room temperature, a cyclohexane / ethanol mixed solution with a volume ratio of 1:3 is added to the black colloidal solution. The solution is then centrifuged at 8500 r / min for 5 min, and then washed twice with the cyclohexane / ethanol mixed solution to obtain a copper sulfide nanosheet-loaded rhenium metal single atom catalyst.

[0093] In this embodiment, the mass concentration of dodecacarbonyl dirhenium is 0.2 mg / mL, and the loading amount of rhenium metal single atoms in the prepared copper sulfide nanosheet-supported rhenium metal single atom catalyst is 0.3 at%;

[0094] The mass concentration of dodecacarbonyl dirhenium is 1 mg / mL, and the loading amount of rhenium metal single atoms in the prepared copper sulfide nanosheet-supported rhenium metal single atom catalyst is 4.2 at%;

[0095] The mass concentration of dodecacarbonyl dirhenium is 2 mg / mL, and the loading amount of rhenium metal single atoms in the prepared copper sulfide nanosheet-supported rhenium metal single atom catalyst is 8.5 at%;

[0096] The mass concentration of dodecacarbonyl dirhenium is 4 mg / mL, and the loading amount of rhenium metal single atoms in the prepared copper sulfide nanosheet-supported rhenium metal single atom catalyst is 12.4 at %.

[0097] Comparative Example 1

[0098] The preparation method is the same as that in Example 1, except that triosmium dodecacarbonyl in Example 1 is replaced by chloroauric acid, and copper sulfide nanosheets loaded with gold metal single atom catalyst cannot be prepared.

[0099] Comparative Example 2

[0100] The preparation method is the same as that in Example 1, except that triosmium dodecacarbonyl in Example 1 is replaced by silver nitrate, and copper sulfide nanosheets loaded with gold and silver single atom catalysts cannot be prepared.

[0101] Comparative Example 3

[0102] 1) dissolving copper acetylacetonate, sulfur powder and triosmium dodecacarbonyl in an organic solvent at concentrations of 2.4 mg / mL, 0.2 mg / mL and 0.2-4 mg / mL (specifically 0.2 mg / mL, 1 mg / mL, 2 mg / mL or 4 mg / mL in this embodiment) respectively, and ultrasonicating for 20 minutes to prepare a uniform colloidal solution;

[0103] 2) The dispersion obtained in step 1 is transferred to an oil bath pot for oil bath heating. After the dispersion is heated to 180° C., it is kept warm. The dispersion is allowed to react at 180° C. for 60 minutes to generate a black colloidal solution. The heating is then stopped. After the reaction container is cooled to room temperature, a cyclohexane / ethanol mixed solution with a volume ratio of 1:3 is added to the black colloidal solution, followed by centrifugation at 9500 r / min for 5 minutes, and then washed twice with a cyclohexane / ethanol mixed solution to obtain the product.

[0104] Comparative Example 4

[0105] 1) dissolving copper acetylacetonate, sulfur powder and triosmium dodecacarbonyl in an organic solvent at concentrations of 2.4 mg / mL, 1.2 mg / mL and 0.2-4 mg / mL (specifically 0.2 mg / mL, 1 mg / mL, 2 mg / mL or 4 mg / mL in this embodiment) respectively, and ultrasonicating for 20 minutes to prepare a uniform colloidal solution;

[0106] 2) The dispersion obtained in step 1 is transferred to an oil bath pot for oil bath heating. After the dispersion is heated to 180° C., it is kept warm. The dispersion is allowed to react at 180° C. for 60 minutes to generate a black colloidal solution. The heating is then stopped. After the reaction container is cooled to room temperature, a cyclohexane / ethanol mixed solution with a volume ratio of 1:3 is added to the black colloidal solution, followed by centrifugation at 9500 r / min for 5 minutes, and then washed twice with a cyclohexane / ethanol mixed solution to obtain the product.

[0107] Fig.10 The transmission electron micrograph of the product obtained when the mass ratio of copper salt to sulfur powder in Comparative Example 3 is 12:1 (sulfur powder is 0.2 mg / mL), Fig.10 It can be seen that the product prepared in Comparative Example 3 is a nanoflower-like structure. Fig.11 The transmission electron micrograph of the product obtained when the mass ratio of copper salt to sulfur powder in Comparative Example 4 is 2:1 (sulfur powder is 1.2 mg / mL). Fig.11 It can be seen that the product prepared in Comparative Example 4 is nanosheets of different sizes. From Comparative Examples 3 and 4, it can be seen that the mass ratio of organic copper salt and sulfur powder is very critical to the morphology of copper sulfide nanosheets. In Comparative Example 2, the mass ratio of copper salt and sulfur powder is 12:1, the copper metal content is too high, and clusters are easily formed to obtain nano flower-like structures; in Comparative Example 4, the mass ratio of copper salt and sulfur powder is 2:1, and the copper metal content is too low, resulting in uneven nanosheets.

[0108] From the above embodiments, it can be seen that the supported metal single atom catalyst provided by the present invention is in the form of a two-dimensional nanosheet, the diameter of the nanosheet is 10-15nm, and the thickness of the sheet is 2-3nm; the platinum group metal supported by the copper sulfide nanosheet exists in the form of a single atom, and the type of the platinum group metal single atom is an iridium single atom, a rhodium single atom, a ruthenium single atom, a platinum single atom or an osmium single atom, and the platinum group metal single atom is coordinated with sulfur without forming a cluster or nanoparticle, and the loading amount of the platinum group metal single atom in the catalyst is 0.3-12.4at%. The supported metal single atom catalyst provided by the present invention has uniform single atom dispersion and high loading amount, and realizes the controllability of the type and loading amount of the metal single atom.

[0109] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A supported metal single atom catalyst, characterized in that: The invention comprises copper sulfide and transition metal single atoms loaded on the surface of the copper sulfide, wherein the transition metal single atoms comprise platinum group metal single atoms and / or rhenium metal single atoms; and the loading amount of the transition metal single atoms is ≥0.3at%.

2. The supported metal single atom catalyst according to claim 1, characterized in that: The platinum group metal single atom includes one or more of an osmium metal single atom, a rhodium metal single atom, a platinum metal single atom, an iridium metal single atom and a ruthenium metal single atom.

3. The supported metal single atom catalyst according to claim 1 or 2, characterized in that: The loading amount of the transition metal single atom is 0.3 to 12.4 at %.

4. The supported metal single atom catalyst according to claim 1, characterized in that The copper sulfide has a diameter of 10 to 15 nm and a thickness of 2 to 3 nm.

5. The method for preparing a supported metal single atom catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: mixing an organic copper salt, sulfur powder, a transition metal organic precursor and an organic solvent to obtain a dispersed solution; The dispersed solution is heated to react to obtain the supported metal single atom catalyst.

6. The preparation method according to claim 5, characterized in that: The organic copper salt is copper acetylacetonate; the transition metal organic precursor includes one or more of iridium acetylacetonate, rhodium acetylacetonate, ruthenium acetylacetonate, platinum acetylacetonate, triosmium dodecacarbonyl and dirhenium dodecacarbonyl; The organic solvent includes one or more of oleic acid, oleylamine, ethylene glycol and benzyl alcohol.

7. The preparation method according to claim 5 or 6, characterized in that: In the dispersed solution, the mass concentration of the organic copper salt is 2-2.5 mg / mL, the mass concentration of the sulfur powder is 0.5-0.6 mg / mL, and the mass concentration of the transition metal organic precursor is 0.2-4 mg / mL.

8. The preparation method according to claim 5, characterized in that: The reaction temperature is 180-220° C., and the insulation time is 60-120 min.

9. The preparation method according to claim 5, characterized in that: After the reaction is completed, a colloidal reaction product is directly obtained; and the method further comprises: post-treating the colloidal reaction product with an organic reagent to obtain the supported metal single atom catalyst; the organic reagent comprises cyclohexane and ethanol, and the volume ratio of cyclohexane to ethanol is 1:1 to 3.

10. Use of the supported metal single atom catalyst according to any one of claims 1 to 4 or the supported metal single atom catalyst prepared by the preparation method according to any one of claims 5 to 9 in energy catalysis.

Citation Information

Patent Citations

  • Preparation method of metal monatomic site catalyst

    CN107626294A

  • Molybdenum disulfide loaded Ir monatomic catalyst as well as preparation method and application thereof

    CN109759093A

  • Application of supported monatomic noble metal catalyst in unsaturated hydrocarbon carboxymethyl esterification reaction

    CN112830877A

  • Method for preparing metal monatomic catalyst by hydrothermal method

    CN114345346A

  • Ruthenium-based stable anode catalysts for water oxidation reaction in acidic electrolytes

    WO2024086742A1